PENINGKATAN NILAI EKONOMIS LIMBAH PRODUKSI JAMUR MERANG MENJADI BRIKET SEBAGAI SUMBER ENERGI ALTERNATIF DI DESA BAYUR KECAMATAN RAJABASA - yuli darni; Herti Utami; Darmansyah Darmansyah; Lia Lismeri; Nandi Haerudin (Jurnal Pengabdian Kepada Masyarakat Sakai Sambayan, 2020)
The paddy straw mushroom is one type of mushrooms that begin to be developed in the village of Bayur. They cultivate the paddy straw mushroom because the commodity, can make a lot of money in the market, the maintenance are relatively easy and cheap with the price quite beneficial. For the media paddy straw mushroom used the empty bunches of oil palm which it was the utilization of waste from palm oil plantations. After several harvests, the paddy straw mushroom replaced with new media. Of the empty bunches of oil palm used, the rest of the media mushroom that become waste that accumulates and difficult to decomposed because of the cellulose and lignin of the empty bunches of oil palm. Increasingly the waste will pollute and containing bacterium of disease. The problems faced by partner is related to the aspects of the provision of energy and management waste processing the rest of the production of mushroom. To overcome the problems, the team provide training the procedure of making briquette and design an instrument print of briquette from the rest of the media of mushroom. This instrument give an advantages for both in the independence of energy and the utilization of the waste production . The method of PKM activity involved the partners (the farmers) in the overall of activities. The outer of this main activity are the instrument print of briquette and to increase the ability and knowledge the partner. The product development briquettes can be used own and sold commercially. With this training, the ability of the partner of the making product briquettes can reduce production cost and to raise the income of partner. Keywords: efficient technology; print of briquettes; waste; media the paddy straw mushroom